Analysis of Geometrical Accuracy of Long Grating Scale Calibration Comparator - Barakauskas, A.; Kasparaitis, A.; Šukys, A; Kojelavičius, P. (Elektronika ir Elektrotechnika, 2008)
Line detection errors in linear scale comparators occur in the cases where Abbe principle is ignored. These errors consist of random and systematic components and can be minimized by increasing the accuracy of component design and production, as well as by compensating geometrical deviations. Design methods intended to increase the accuracy of the precision movement of comparator parts are described here. Experimental error investigation results are presented. Computational and active methods of geometrical errors compensation are established and described. Investigation results are arranged and efficiency of the examined methods is compared. Ill. 4, bibl. 5 (in English; summaries in English, Russian and Lithuanian).